Compression Effects on Structural Relaxation Process of Amorphous Indomethacin - Cuong, Tran Dinh; Phan, Anh D. (Communications in Physics, 2021)
Indomethacin is a common nonsteroidal anti-inflammatory drug, but its glass transition behaviors remain ambiguous. Here we present a simple theoretical approach to investigate the molecular mobility of amorphous indomethacin under compression. In our model, the relaxation of a particle is governed by its nearest-neighbor interactions and long-range cooperative effects of fluid surroundings. On that basis, the temperature and pressure dependence of the structural relaxation time is deduced from the thermal expansion process. Additionally, we also consider correlations between the activated dynamics and the shear response in the deeply supercooled state. Our numerical calculations agree quantitatively well with previous experimental works